Pengaruh Koordinasi Terhadap Keselamatan Penerbangan di Airnav Indonesia Cabang Balikpapan - Muhammad Iqbal; Endang Sugih Arti; Weda Yuwana (Langit Biru: Jurnal Ilmiah Aviasi, 2021)
This study aims to obtain an overview of whether there is an influence between the coordination with flights at the Balikpapan branch of the LPPNPI Perum. The research was carried out at Perum LPPNPI Balikpapan Branch and the data processing was carried out at the Indonesian Aviation Polytechnic Curug - Tangerang requested from January 2020 to July 2020. The method used was quantitative research methods. Which method regulates the data using a questionnaire / questionnaire, and with a sample of 31 respondents and an error rate of 5% addressed to ATC personnel at the Balikpapan branch of LPPNPI Public Corporation. The study concludes that it is known that there is a significant relationship and influence between coordination and flight safety with simple regression analysis showing a significance value of 0.000 which is less than α = 0.025 and t-count = 15.342 which is greater than t-table 2.04523, therefore the decision is Ho is rejected, so it can be said that there is an influence between coordination (X) on flight safety (Y).